Awareness and Attitudes of Medical Students, Interns, and Residents Toward Telemedicine in Medical Education During the COVID-19 Pandemic: Survey-Based Cross-Sectional Study From Northern Iran - Rahmat Allah Sharififar; Mahdi Mazandarani; Narges Lashkarbolouk; Somayeh Ghorbani (Journal of Medical Education and Curricular Development)
BACKGROUND Telemedicine is widely used in medical treatment and education systems. Therefore, it is essential to investigate the attitudes and awareness of medical students about it. We aimed to examine the awareness and attitudes of medical students, interns and residents toward telemedicine in medical education during the COVID-19 pandemic. METHOD This cross-sectional study was conducted after new educational approaches were implemented due to the COVID-19 pandemic. Two questionnaires were used to assess the new educational methodologies. Participants included residents (R), interns (I), and students (S) from the internal medicine department. A census sampling method was employed, inviting all medical education members who met the entry criteria to participate. The data were analyzed descriptively, and group differences were tested using chi-square, independent samples T-test, Mann–Whitney, and Kruskal–Wallis tests. RESULT Out of 278 medical education members eligible to participate, 249 (89.5%) completed the study. The mean score for participants’ attitudes was above 3 ( M  = 3.78, SD  = 0.24) indicating a generally favorable view of telemedicine. A significant gap was noted between participants’ awareness and attitudes, with residents showing the lowest scores in both areas ( P -value = .02). Our assessment revealed that “Satisfaction with the platform and facilities for e-classes” received the highest consensus from residents and interns, rated moderately agreeable by students (R: 64.5%, I: 59.7%, S: 48.8%). Responses to “Using e-learning courses alongside postcrisis face-to-face courses” and “Using e-learning courses alone postcrisis” varied among the groups (R: 58.1% and 54.9%, I: 59% and 58.2%, S: 47.6% and 45.3%). CONCLUSION The results of this survey reveal that medical students and interns may demonstrate a favorable awareness and attitude toward telemedicine. Consequently, developing educational programs and enhancing exposure to telemedicine should be considered since these elements could be vital for the future training of medical professionals.